The Pro-Apoptotic Proteins, Bid and Bax, Cause a Limited Permeabilization of the Mitochondrial Outer Membrane That Is Enhanced by Cytosol - Kluck, Ruth M. (The Rockefeller University Press, 1999)
During apoptosis, an important pathway leading to caspase activation involves the release of cytochrome c from the intermembrane space of mitochondria. Using a cell-free system based on Xenopus egg extracts, we examined changes in the outer mitochondrial membrane accompanying cytochrome c efflux. The pro-apoptotic proteins, Bid and Bax, as well as factors present in Xenopus egg cytosol, each induced cytochrome c release when incubated with isolated mitochondria. These factors caused a permeabilization of the outer membrane that allowed the corelease of multiple intermembrane space proteins: cytochrome c, adenylate kinase and sulfite oxidase. The efflux process is thus nonspecific. None of the cytochrome c-releasing factors caused detectable mitochondrial swelling, arguing that matrix swelling is not required for outer membrane permeability in this system. Bid and Bax caused complete release of cytochrome c but only a limited permeabilization of the outer membrane, as measured by the accessibility of inner membrane-associated respiratory complexes III and IV to exogenously added cytochrome c. However, outer membrane permeability was strikingly increased by a macromolecular cytosolic factor, termed PEF (permeability enhancing factor). We hypothesize that PEF activity could help determine whether cells can recover from mitochondrial cytochrome c release.